Impact of Mitochondrial Permeability on Endothelial Cell Immunogenicity in Transplantation. Issue 6 (June 2018) - Tran, Danh T.; Esckilsen, Scott; Mulligan, Jennifer; Mehrotra, Shikhar; Atkinson, Carl; Nadig, Satish N.
Abstract : Background: Microvascular endothelial cells (ECs) are central to an allograft's immunogenicity. Cold ischemia and reperfusion injury associated with static cold storage and warm reperfusion activates ECs and increases the immunogenicity of the allograft. After reperfusion, mitochondrial permeability transition pore (mPTP) opening contributes to mitochondrial dysfunction in the allograft, which correlates to alloimmune rejection. Current understanding of this relationship, however, centers on the whole allograft instead of ECs. This study aimed to elucidate the relationship between EC mPTP opening and their immunophenotype. Methods: Mitochondrial metabolic fitness and glycolysis in ECs were assessed in parallel with metabolic gene microarray postreperfusion. NIM811 was used to inhibit mPTP opening to rescue mitochondrial fitness. The immunogenicity of NIM811-treated ECs was determined via levels of EC's proinflammatory cytokines and allogeneic CD8 + T cell cocultures. Finally, EC surface expression of adhesion, costimulatory, coinhibitory, MHC-I molecules, and MHC-I machinery protein levels were characterized. Results: Genes for glycolysis, tricarboxylic acid cycle, fatty acid synthesis, gluconeogenesis were upregulated at 6 hours postreperfusion but either normalized or downregulated at 24 hours postreperfusion. As mitochondrial fitness was reduced, glycolysis increased during the first 6 hours postreperfusion. Endothelial cell treatment with NIM811 during the early postreperfusion period rescued mitochondrial fitness and reduced EC immunogenicity by decreasing CCL2, KC release, and VCAM-1, MHC-I, TAP1 expression. Conclusions: Static cold storage and warm reperfusion leads to a reduction in mitochondrial fitness in microvascular ECs due to mPTP opening. Further, mPTP opening promotes increased EC immunogenicity that can be prevented by NIM811 treatment. Abstract : Cold storage and warm reperfusion of endothelial cells result in decreased mitochondrial fitness and increased glycolysis as well as immunogenicity. Treatment with NIM811, an inhibitor of mitochondrial permeability transition pores, reduced these effects. Supplemental digital content is available in the text.